The effects of price on product’s perceived risk and overall benefits in B2B contexts - Saab, André Bueno (2017)
B2B price scholarship most frequently assumes that organizational purchase is a rational, free-bias activity, in line with theory of choice. Heuristics, such as price-quality effect, are rarely applied in theories, frames and models to explain how purchase managers respond to price stimuli. However, new studies in B2B sets have been suggesting that price response may not be as rational as the prevailing perspective had assumed. Trying to shed light on the issue of behavioral response to price stimuli in B2B sets, this study undertook a laboratory experiment to test the effects of price on product’s perceived risk (as the uncertainty of adverse outcome due to purchase decision) and product’s overall benefits. This experiment also tested as possible moderators (i) decision importance, (ii) experience at buying tasks and (iii) product type (search vs. credence). Findings gave support to the behavioral hypothesis that managers do take price to make judgments about product’s perceived risk (main effect), effect known as price-quality effect, one kind of heuristic. None of the proposed moderators could individually moderate the main effect. However, experience in buying tasks and product type could simultaneously moderate the main effect, in a second order interaction, but not exactly as hypothesized. Experienced managers, under search products judgment, as well as inexperienced managers, under credence products judgment, took price to make inferences on product’s perceived risk. The main conclusions are that (i) organizational price response is not as rational and bias free as the prevailing perspective had assumed and (ii) moderation of price-quality effect in B2B is more complex and sophisticated than previous studies had proposed. Finally, the study discusses implications for theory building and price management in B2B.